A note on convergence of weighted sums of random variables. (1985) - Wang, Xiang Chen; Rao, M. Bhaskara
Abstract : Under uniform integrability condition, some Weak Laws of large numbers are established for weighted sums of random variables generalizing results of Rohatgi, Pruitt and Khintchine. Some Strong Laws of Large Numbers are proved for weighted sums of pairwise independent random variables generalizing results of Jamison, Orey and Pruitt and Etemadi.